2020
DOI: 10.1177/1045389x20919979
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrode configuration on impact damage evaluation of self-sensing hierarchical composites

Abstract: A technique based on the electrical resistance change of a network of carbon nanotubes within a polymer composite was implemented to assess damage caused by low-velocity impact in multiscale hierarchical composites. The influence of the electrode configuration in 100 mm x 100 mm x 1.7 mm plates is addressed. Three electrode configurations are evaluated, namely, a grid on the impacted surface, a grid on the opposite (non-impacted) surface, and through the thickness of the plate. Upon impact, matrix cracking, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In the process of manufacturing, use, and maintenance of composites, they will inevitably suffer from the impact and collision by external objects or unexpected environments, thus causing structural damage to specimens 14,15 . When the impact load is applied, damage modes such as matrix depression/fracture, fiber breakage, delamination, and perforation will occur, and these damage modes interact and couple to each other 16,17 . It has been widely reported that the residual mechanical properties of the composites will be greatly reduced after impact injury, 18,19 and the influence of residual tensile properties of nonwoven flax fiber‐reinforced composites under different impact energies was demonstrated by Habibi et al 20 Dhakal et al 21 studied the effects of mechanical properties of cannabis/basalt fiber‐reinforced composites after the impact, and the initial stage of the impact caused obvious damage in the form of matrix cracking and fiber fracture, which significantly reduced the residual strength after the impact.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of manufacturing, use, and maintenance of composites, they will inevitably suffer from the impact and collision by external objects or unexpected environments, thus causing structural damage to specimens 14,15 . When the impact load is applied, damage modes such as matrix depression/fracture, fiber breakage, delamination, and perforation will occur, and these damage modes interact and couple to each other 16,17 . It has been widely reported that the residual mechanical properties of the composites will be greatly reduced after impact injury, 18,19 and the influence of residual tensile properties of nonwoven flax fiber‐reinforced composites under different impact energies was demonstrated by Habibi et al 20 Dhakal et al 21 studied the effects of mechanical properties of cannabis/basalt fiber‐reinforced composites after the impact, and the initial stage of the impact caused obvious damage in the form of matrix cracking and fiber fracture, which significantly reduced the residual strength after the impact.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, carbon nanostructures can reach small interstices and interfaces of the multiscale material, making the technique sensitive not only to fiber damage 14 but also to interfacial damage 22,28 and other failure modes such as delamination. 14,29 This technique has been employed to assess damage inflicted by tensile, 21,30 bending, 14,23,31 and impact loading, 22,24,25 mostly under monotonic loading up to failure. The technique has also been proved effective for cycling loading, 14,21,23,31 although reports on cycling loading are scarcer.…”
Section: Introductionmentioning
confidence: 99%
“…14,16,17 Carbon fibers were first used to this aim, 10,16,[18][19][20] but their sensitivity was found to be very limited, and the technique is poorly sensitive to damage occurring in the matrix. 16,18 As an alternative, carbon nanostructures, such as carbon nanotubes (CNTs) or graphenic sheets, have been used to modify either the fibers 9,11,14,[21][22][23][24] or the polymeric matrix [20][21][22][24][25][26] of advanced polymer composites. Upon achieving a minimum electrical conductivity (just above electrical percolation) in the composite, the electrical conductivity (or resistance) of the material becomes sensitive to the inflicted damage.…”
Section: Introductionmentioning
confidence: 99%
“…Properly selected methods of dynamic parameter modelling used in damage detection algorithms allow for a various analysis to be carried out with the purpose of optimising these diagnostic methods. This process can cover many aspects, like: assessment of the FE model sensitivity [32]; analysis of the measurement signal in order to locate damage [33]; assessment of the effectiveness of a damage detection technique in terms of the density of the measurement grid [34][35][36][37][38] and the analysis of the influence of the location of the sensor grid on the proposed methodology correctness [39][40][41].…”
Section: Introductionmentioning
confidence: 99%